2007
DOI: 10.4049/jimmunol.178.10.6290
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant Hypoallergenic Parvalbumin Mutant for Immunotherapy of IgE-Mediated Fish Allergy

Abstract: IgE-mediated allergy to fish is a frequent cause of severe anaphylactic reactions. Parvalbumin, a small calcium-binding protein, is the major fish allergen. We have recently isolated a cDNA coding for carp parvalbumin, Cyp c 1, and expressed in Escherichia coli a recombinant Cyp c 1 molecule, which contained most IgE epitopes of saltwater and freshwater fish. In this study, we introduced mutations into the calcium-binding domains of carp parvalbumin by site-directed mutagenesis and produced in E. coli three pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
0
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(139 citation statements)
references
References 44 publications
3
126
0
10
Order By: Relevance
“…Table 3 shows the IC 50 values which ranged from 0.20 to 0.41 mg/mL. Attempts to make allergen extracts or allergens hypo-allergenic, for example by chemical modification or biotechnological modification, aim to reduce the IgE-binding at least 100-fold, preferably more (Apostolovic et al, 2013;Ibarrola et al, 2004;Swoboda et al, 2007;van Bilsen et al, 2013;Versteeg et al, 2011). The narrow range of IC 50 values reported here (only a 2-fold difference) indicates that the peanut samples have a highly comparable IgE-binding potency.…”
Section: Reactivity In Ige-binding Assaymentioning
confidence: 99%
“…Table 3 shows the IC 50 values which ranged from 0.20 to 0.41 mg/mL. Attempts to make allergen extracts or allergens hypo-allergenic, for example by chemical modification or biotechnological modification, aim to reduce the IgE-binding at least 100-fold, preferably more (Apostolovic et al, 2013;Ibarrola et al, 2004;Swoboda et al, 2007;van Bilsen et al, 2013;Versteeg et al, 2011). The narrow range of IC 50 values reported here (only a 2-fold difference) indicates that the peanut samples have a highly comparable IgE-binding potency.…”
Section: Reactivity In Ige-binding Assaymentioning
confidence: 99%
“…Sequential IgE epitopes are rare and have been described mainly for food allergens, which may be due to the fact that true food allergens undergo proteolysis in the gastrointestinal tract before they induce an IgE sensitization. However, it has been shown that true food allergens also contain conformational epitopes (9)(10)(11). Several lines of evidence support the concept that IgE epitopes represent mainly conformational epitopes.…”
mentioning
confidence: 98%
“…Carp parvalbumin (Cyp c 1) contains most cross-reactive IgE epitopes present in the family of homologous fish parvalbumin. [23] In 2007, a mutant (m) Cyp c 1, [24] was created with the two functional Ca 2+ -binding sites mutated, rendering the molecule hypoallergenic. As in many similar papers, the tentative conclusion: "this molecule might be an interesting candidate for future immunotherapy" was proposed.…”
Section: Hypoallergenic Molecules For Subcutaneous Immunotherapymentioning
confidence: 99%